Designing an Uno-Based English Game to Enhance Speaking Skills of Eighth Grade Students - Nokiana, Rita; Mubarok, Tyas Alhim; Rofiah, Siti (PROJECT (Professional Journal of English Education), 2025)
This study seeks to create an educational game called the UNO English Game as an innovative learning tool to enhance the speaking abilities of eighth-grade students. The research adopts the Research and Development (R&D) approach, used the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The game was created by adapting the traditional UNO card game and integrating it with English learning content focused on speaking activities such as asking and answering questions, describing, and expressing opinions. The results of the implementation show that the UNO English Game enhances students’ engagement, motivation, and confidence in speaking English. It also provides a fun and interactive learning environment that encourages students to practice speaking more actively. Based on the findings, the UNO English Game is considered an effective supplementary tool for enhancing speaking skills in junior high school English classes.